Continuous magnetotelluric observations in Western Crete as a tool for the study of the Hellenic subduction Zone - Kalisperi, D.; Rigakis, I.; Makris, J.P.; Romano, G.; Vallianatos, F. (Bulletin of the Geological Society of Greece, 2013)
In the frame of the “MagnetoTellurics in studying Geodynamics of the hEllenic ARc (MT-GEAR)” project, a new continuous monitoring Magnetotelluric (MT) station has been installed in Western Crete. The new permanent MT-station, designed and constructed incorporating contemporary technology, is solar powered, fully telemetric, and the data transfer can be performed alternatively through 3G network or a satellite link. The selected site for the installation resulted from an exploratory MT survey, among other prospective sites aggregating MT qualifications. The purpose of the operation of a permanent MT observatory is twofold. The primary objective is to act as remote reference station to the ongoing MT survey (at selected Islands of southern Aegean) of the geodynamics of the Hellenic Subduction Zone. In addition, possible apparent resistivity variations as well as electric and/or magnetic field transient anomalies are investigated, while it would be attempted to associate these variations with seismic activity.